Le Nigeria et la Suisse, des affaires d'indépendance - Page, Steve (Peter Lang International Academic Publishing Group, 2016)
During Nigeria's decolonization, Swiss traders and diplomats, aware of the exceptional potential for growth, attentively observed this new market for possible business opportunities. This book focuses on multinational companies, diplomats, development cooperation actors and public opinion: it analyses underlying motivations and means, as well as the implications of their activities.